2006
DOI: 10.1248/bpb.29.1006
|View full text |Cite
|
Sign up to set email alerts
|

Buformin Suppresses the Expression of Glyceraldehyde 3-Phosphate Dehydrogenase

Abstract: Three biguanides, phenformin, buformin, and metformin, were first used clinically for diabetes mellitus in the 1950s. Since phenformin was found to have a lethal side effect, lactic acidosis, in the late of 1970s, 1) its usage decreased rapidly in many countries and was finally withdrawn. Then use of other biguanides declined gradually because of their own adverse effects. Lactic acidosis, hypoglycemia, and digestive organ dysfunction have been found to be adverse effects of biguanides. Lactic acidosis caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Since that time a number of papers has shown that in primary tumors or tumor cell lines connexins can be downregulated or even be absent, that oncogenes or cancerogenic drugs often inhibit gap junction channel function or reduce connexin expression (Loewenstein and Kanno, 1966; Trosko et al, 1990; Lampe, 1994; Laird et al, 1999; Mesnil et al, 2005; Salameh and Dhein, 2005; Cronier et al, 2009). However, on the other hand, some researchers found a role of gap junctions promoting invasion, cell extravasation, and migration of tumor cells (Naoi et al, 2007; Saito-Katsuragi et al, 2007; Ezumi et al, 2008), while others do not support this view (Yano et al, 2006; Sato et al, 2008). This lead to the interpretation that connexins might be “differentially regulated during the dissemination of specific tumor types” (Naus and Laird, 2010), and that down-regulation of connexin in early tumors might be linked to invasion, but in later states elevation in connexins can occur facilitating extravasation and formation of secondary tumors (Naus and Laird, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since that time a number of papers has shown that in primary tumors or tumor cell lines connexins can be downregulated or even be absent, that oncogenes or cancerogenic drugs often inhibit gap junction channel function or reduce connexin expression (Loewenstein and Kanno, 1966; Trosko et al, 1990; Lampe, 1994; Laird et al, 1999; Mesnil et al, 2005; Salameh and Dhein, 2005; Cronier et al, 2009). However, on the other hand, some researchers found a role of gap junctions promoting invasion, cell extravasation, and migration of tumor cells (Naoi et al, 2007; Saito-Katsuragi et al, 2007; Ezumi et al, 2008), while others do not support this view (Yano et al, 2006; Sato et al, 2008). This lead to the interpretation that connexins might be “differentially regulated during the dissemination of specific tumor types” (Naus and Laird, 2010), and that down-regulation of connexin in early tumors might be linked to invasion, but in later states elevation in connexins can occur facilitating extravasation and formation of secondary tumors (Naus and Laird, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In addition, buformin has been proposed to be more appealing since it shows greater lipophilicity and the ability to inhibit mitochondrial complex I and thereby suppress ATP production. 29,30 Thus, we first investigated the efficacy of buformin to treat cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin was reported to raise the intracellular ratio of NADH to NAD ϩ . 9,31) This increase was proposed to result in less lactate being converted to pyruvate by lactate dehydrogenase causing the lactate to accumulate. 32) Since pyruvate is produced not only by glycolysis but also by gluconeogenesis via an intermediate in the citric acid cycle, the reaction equilibrium catalyzed by lactate dehydrogenase appears to shift towards lactate production.…”
Section: Discussionmentioning
confidence: 99%
“…9) Since GAPD is included in the glycolytic pathway, the decreased expression of GAPD is suggested to cause the accumulation of lactic acid and result in lactic acidosis. GAPD is frequently used as a housekeeping gene for the quantitative measurement of gene expression.…”
mentioning
confidence: 99%